Assessment of left ventricular functions by strain and strain rate echocardiography in asymptomatic type II diabetic patients - Mohamed Mahmoud (Wolters Kluwer Medknow Publications, 2019)
Background and aim The chronic hyperglycemia of diabetes is associated with long-term damage, dysfunction, and failure of various organs, especially the eye, kidneys, heart and blood vessels, as treatment to reverse this disorder is more likely to be effective at an early (preclinical) stage, defining the mechanism of diabetic cardiomyopathy may be important to its selective treatment. Aim To assess the left ventricle (LV) function using tissue Doppler (TD) strain and strain rate imaging to detect early LV functions affection in type II diabetic patients without overt heart disease. Patients and methods The study included 60 persons presented in Al Azhar University (Asyut branch) Hospital in the period between November 2014 and January 2016. Were divided into two groups: group (1): 30 diabetic patients with normal (ejection fraction) EF and normal coronaries, group (2): 30 individual without diabetes mellitus (DM) with normal EF as a control group. The following was done for the two groups: 1. Complete History taking and complete general and cardiac clinical examination, resting 12 leads electrocardiography (ECG). 2. Laboratory investigation to diagnose diabetes and the control of the disease. 3. Transthoracic echo examination: 4. TD Strain and strain rate of the LV. Results In comparison between group (1) and group (2) the LV strain and strain rate was found to be significantly lower in group (1) as compared to group (2). Among group I, duration of DM was significantly correlated with decreased strain rate in posterior septum only. There was no correlation between methods of control and the degree of control and the impairment of strain and strain rate. From the present study we found that left ventricular strain and strain rate by conventional echo could reveal the presence of subclinical diabetic cardiomyopathy. Conclusions Type 2 DM deteriorates both LV systolic and diastolic performance. Diabetic patients showed some changes in strain and SR of LV walls at rest especially when the duration of diabetes increased. Strain and SR by TD is superior to conventional Doppler in early detection and evaluation of systolic and diastolic dysfunction in type 2 diabetic patients.